The Role of Artificial Intelligence in Curriculum Development at the Tertiary Education Level - Nkolika, Chukwuka Judith (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: The integration of Artificial Intelligence (AI) into higher education has the potential to enhance teaching and learning processes. However, its implementation is often hindered by various contextual and institutional factors, especially in developing regions such as Anambra State, Nigeria. Objective: This study aimed to investigate the challenges and factors influencing lecturers' teaching practices and professional competency needs in tertiary institutions within Anambra State, particularly in relation to the integration of AI in education. Method: A descriptive survey design was employed. Data were collected using a structured questionnaire distributed online via Google Forms to 62 lecturers. The instrument, divided into demographic and five-point Likert scale sections, was validated by experts and pilot-tested, yielding a reliability score of 0.85 (Cronbach’s alpha). Data analysis was conducted using SPSS version 23, involving descriptive statistics (frequencies, percentages, means, and standard deviations) and inferential statistics (ANOVA). Result: Findings revealed that AI has several advantages, including personalized learning experiences, data-driven curriculum optimization, and enhanced instructional efficiency. Nonetheless, major challenges were identified, such as limited access to high-quality data, high implementation costs, lack of technical expertise, and educator resistance. Conclusion: While AI holds significant promise for improving tertiary education, its effective adoption requires addressing systemic barriers and equipping educators with the necessary skills and support. Contribution: This study provides practical insights for policymakers and educators to support the integration of AI into curriculum planning. It highlights the need for strategic investments in infrastructure, continuous training, and ethical frameworks to ensure effective and equitable implementation.